PERKEMBANGAN KONSELING PADA ABAD 21: KONSELOR SEBAGAI PROFESI YANG MENGEDEPANKAN TANGGUNG JAWAB KEHIDUPAN EFEKTIF KONSELI - Kushendar Kushendar; Aprezo Pardodi Maba; Indah Fajrotuz Zahro (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
Guidance and counseling in Indonesia has been established since the 1970s. Despite all the obstacles in it’s aplication, guidance and counseling continuously to develop. Since that counselor profession has taken a role in order to serve optimizing the potency of the counselee. Along with the globalization, the role of the counselor becomes increasingly important, in conjunction with the problems faced by the counselor. Goverment through professional organization have develop a standardized guideline to meet the inherent expectations of the counselor profession. Through this article the authors try to describing an overview of the responsibilities that should met by the counselor in various settings as an effort to maintain and improvethe counselee wellbeing